DEVELOPMENT OF LEARNING MEDIA BASED ON WINDOWS PRODUCERS TO IMPROVE STUDENT METACOGNITIONAL AWARENESS - Nova Dwi Pratiwi Sulastri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2020)
The study was Research and Development which animed at examining the validity, development, implementation, and evaluation. Data obtained from study were (1) validity data obtained through evaluation from the experts and practitioners, practicality data obtained through quiestionnaire of students, (3) effectiveness data obtained through quiestinnaire of students, (4) metacognitive awareness data obtained quiestionnaire of MAI instrument. The result of the data revealed that Windows produser-based learning media on Biologi subject to enhance awareness and students’ metacognitive skill which was development had achieved the quality criteria: (1) Windows produser-based learning media on reproduction system concept validity meets the criteria stated, practicality and effectiveness, (3) Windows produser-based learning media on reproduction system concept can increase student’s awareness metacognition Keyword: Research development, Windows Producer, awareness metacognition and Reproduction System